2015
DOI: 10.1007/s10800-015-0876-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of a Sb-doped SnO2 support synthesized by coprecipitation for oxygen reactions

Abstract: Highly dispersed platinum or platinum-based catalysts on a conductive support are commonly used as electrode materials in low-temperature fuel cells. Similarly, iridium oxide is the usual anode material in polymeric exchange membrane electrolyzers. The performance and, in particular, the stability of these catalysts strongly depends on the characteristics of the support. This study presents the results of the physicochemical and electrochemical characterization of the powers of antimony-doped tin oxide (ATO) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The bulk conductivities of Nb-doped samples are still very low and far from that of Vulcan XC-72. In agreement with other studies [9,31,33,36,46,47], an impressive improvement in conductivity was observed for Sb-doped SnO 2 ( Table 5). X6SS100 (10 at.% Sb-doped SnO 2 xerogel) shows indeed the typical behavior of a conducting material (Fig.…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…The bulk conductivities of Nb-doped samples are still very low and far from that of Vulcan XC-72. In agreement with other studies [9,31,33,36,46,47], an impressive improvement in conductivity was observed for Sb-doped SnO 2 ( Table 5). X6SS100 (10 at.% Sb-doped SnO 2 xerogel) shows indeed the typical behavior of a conducting material (Fig.…”
Section: Chemical Compositionsupporting
confidence: 92%
“…However, electrochemical characteristics, like the electrochemical surface area (ECSA) or the oxygen reduction reaction (ORR) mass and specific activities of Pt/SnO 2 electrocatalysts, are relatively low compared to those of Pt/C, mostly due to their poor electronic conductivity and low specific surface area. Recent studies have shown the potential of doping SnO 2 by Nb 5+ [26][27][28][29] or Sb 5+ [26,27,[30][31][32][33][34][35][36]. In addition to improving electronic conductivity, dopants are known to inhibit particle growth [37] and modify the material's morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the influence of antimony tin oxide (Sb 2 O 5 /SnO 2 -ATO) on the activity of Pt nanoparticles were carried out for alcohol oxidation [36][37][38][39] and oxygen reduction [40][41][42]. For Pd nanoparticles, the effect of ATO was investigated only for hydrogen peroxide reduction [43] and acid formic oxidation [44].…”
Section: Introductionmentioning
confidence: 99%
“…Antimony‐doped tin oxide (ATO) is one of the most investigated electrocatalyst supports, owing to its electrical conductivity, which is similar to that of carbon . Microporous antimony‐doped SnO 2 supports synthesised through hydrazine reduction and catalysed with platinum nanoparticles showed improved stability at high potential (only 5 % loss of surface area after 300 cycles at 1.45 V), but lower electrocatalytic activity than Pt/C catalysts .…”
Section: Introductionmentioning
confidence: 99%